(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2014)
Gastrointestinal tuberculosis is quite rare, representing only 3% of all extrapulmonary cases. Primary tuberculosis of the appendix is a clinical rarity. It is usually secondary to tuberculosis elsewhere in the abdomen. Diagnosis is often made only after histopathological examination of the resected specimen. This report describes a 21 year old male with clinical diagnosis of acute appendicitis, who was finally diagnosed as tuberculous appendicitis as the histopathological examination revealed chronic granulomatous inflammation along with caseous necrosis. We made a diagnosis of primary tuberculosis of appendix and the patient was on anti-tuberculosis medication. This article stresses the importance of histopathological examination of the resected appendix. JCMCTA 2014 ; 25 (2) : 54-56